Stiff matrix induces exosome secretion to promote tumour growth - Wu, Bin; Liu, Di-Ao; Guan, Lei; Myint, Phyoe Kyawe; Chin, LiKang; Dang, Hien; Xu, Ye; Ren, Jinqi; Li, Ting; Yu, Ziyan; Jabban, Sophie; Mills, Gordon B.; et al. (Nature cell biology, 2023)
Tissue fibrosis and extracellular matrix (ECM) stiffening promote tumour progression. The mechanisms by which ECM regulates its contacting cells have been extensively studied. However, how stiffness influences intercellular communications in the microenvironment for tumour progression remains unknown. Here we report that stiff ECM stimulates the release of exosomes from cancer cells. We delineate a molecular pathway that links stiff ECM to activation of Akt, which in turn promotes GTP loading to Rab8 that drives exosome secretion. We further show that exosomes generated from cells grown on stiff ECM effectively promote tumour growth. Proteomic analysis revealed that the Notch signalling pathway is activated in cells treated with exosomes derived from tumour cells grown on stiff ECM, consistent with our gene expression analysis of liver tissues from patients. Our study reveals a molecular mechanism that regulates exosome secretion and provides insight into how mechanical properties of the ECM control the tumour microenvironment for tumour growth. Wu et al. report that a stiff extracellular matrix stimulates the release of exosomes from cancer cells under the control of Akt and Rab8. These exosomes in turn promote tumour growth.